PEMAKAIAN KOSAKATA BAHASA INGGRIS DI SURAT KABAR MANADO POST - LAKADA, ELISABETH M. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research entitled "The Use of English Vocabulary in Manado Post Newspaper". The aims of this research are to describe the cause of the use of English vocabulary in Manado post Newspaper and to describe the function of English vocabulary in Manado post Newspaper. The data were collected from Manado Post Newspaper April to May 2016 edition. The method proposed by Sudaryanto that consist of three stages namely, data collection, data analysis, and data presentation was the research method. The data were collected by using translation and comprehend method, whichthe sentences in Manado post Newspaper that contain English vocabulary will be collected. Then,the data will be recorded by using noted method. The method of analysis in this study is to translate the English vocabulary into Indonesian or to find the equivalent vocabulary in the existing data. By doing so, it can be traced the reason and function of the collected and translated data. The results of the analysis showed that the use of English vocabulary because it is considered more practical, met the registers in the Indonesian and considered to have more semantis adequacy. The function of English vocabulary is to show identity and as a tool of cultural implementation. Keywords: Vocabulary, English, Function.